Corporate social responsibility and financial performance: managerial ownership as the moderating variable - Theresia Angelina Susanto; Akhmad Samsul Ulum; Dina Amalia Mahmudah (Universitas Pekalongan, 2024)
This research aims to provide empirical evidence about the influence of corporate social responsibility (CSR) on financial performance, with managerial ownership as a moderating variable. The sample in this research is property and real estate companies that registered with Exchange Effect Indonesia in the years 2016–2020. Sample study This is a total of six companies with 30 observations. Analysis of this research data using SEM-PLS. The results of the study with SEM-PLS show that CSR is influential and positive for performance finance, which is measured by ROE and growth income. Managerial ownership cannot moderate the relationship between CSR and financial performance, which is measured using ROE, but managerial ownership is able to moderate the connection between CSR and performance finance, which can be measured using growth income.